2019
DOI: 10.1111/sms.13544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta2‐adrenergic agonist and resistance training on maximal oxygen uptake and muscle oxidative enzymes in men

Abstract: While beta2‐adrenoceptor stimulation has been shown to increase lean mass and to alter metabolic properties of skeletal muscle, adaptations in muscle oxidative enzymes and maximal oxygen uptake (trueV˙O2max) in response to beta2‐adrenergic agonist treatment are inadequately explored in humans, particularly in association with resistance training. Herein, we investigated beta2‐adrenergic‐induced changes in trueV˙O2max, leg and arm composition, and muscle content of oxidative enzymes in response to treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Likewise, daily inhalation of 4 mg terbutaline for 4 weeks has been shown to decrease maximal oxygen uptake and exercise capacity, regardless of whether subjects maintained their activity level or performed a period of resistance training . In the same studies, it was observed that terbutaline blunted up‐regulation of mitochondrial proteins in skeletal muscle induced by endurance training and lowered the expression of mitochondrial proteins in subjects that maintained their activity level or undertook a resistance training program . These observations are consistent with some rodent studies showing that beta 2 ‐agonist treatment can be associated with detrimental effects on oxidative capacity …”
Section: Antidoping Regulations Adverse Analytical Findings and Abussupporting
confidence: 82%
See 2 more Smart Citations
“…Likewise, daily inhalation of 4 mg terbutaline for 4 weeks has been shown to decrease maximal oxygen uptake and exercise capacity, regardless of whether subjects maintained their activity level or performed a period of resistance training . In the same studies, it was observed that terbutaline blunted up‐regulation of mitochondrial proteins in skeletal muscle induced by endurance training and lowered the expression of mitochondrial proteins in subjects that maintained their activity level or undertook a resistance training program . These observations are consistent with some rodent studies showing that beta 2 ‐agonist treatment can be associated with detrimental effects on oxidative capacity …”
Section: Antidoping Regulations Adverse Analytical Findings and Abussupporting
confidence: 82%
“…In the same study, the hypertrophic response to terbutaline was similar in slow‐ and fast‐twitch muscle fibers of the vastus lateralis, increasing by 15% and 13%, respectively . The anabolic effect of terbutaline also seems to occur to the same extent in the upper and lower extremities, and irrespective of concurrent resistance training, whereas endurance training, notably, has been shown to blunt the anabolic effect of terbutaline – the latter of which is consistent with the interaction between endurance training and beta 2 ‐agonist observed in rodents . Aside from these effects, terbutaline increases metabolic rate and induces lipolysis …”
Section: Anabolic and Lipolytic Effects Of Beta2‐agonistssupporting
confidence: 66%
See 1 more Smart Citation
“…Clenbuterol has been reported to be an effective stimulant for skeletal muscle hypertrophy in rodents . In humans, skeletal muscle hypertrophy has been reported after chronic treatment with other beta 2 ‐agonists, but only a few studies have investigated the effect of chronic clenbuterol treatment. Maltin et al reported increases in muscle strength after 4 weeks of postoperative recovery with clenbuterol treatment (40 μg/day) compared with a placebo group, and Koeberl et al reported increases in functional tests after 52 weeks of clenbuterol treatment (up to 160 μg/day) in patients with Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
“…A continuously growing body of evidence exists that the aerobic performance does not appear to be acutely affected by the use of β 2 ‐agonists such as terbutaline 126–128 . Conversely, β 2 ‐agonists such as salbutamol and salmeterol can enhance anaerobic performance concerning disciplines such as, for example, sprint 129–131 but not necessarily when used at dosages permitted according to WADA's regulations 132 .…”
Section: β2‐agonistsmentioning
confidence: 99%